Caracterização química e atividade acaricida de óleos essenciais da família Lamiaceae no controle do Tetranychus urticae (Koch, 1836) - Moura, Ludmila Vieira (2023)
Over the years, new technologies have been developed, seeking to minimize the effects of pests in agriculture. An example of these technologies is the use of synthetic-based pesticides to control pests. However, due to the high toxicity of these products, alternative forms of pest management have been the subject of several studies. An alternative to agricultural pesticides is the use of essential oils as biopesticides. Such oils, due to their chemical composition, have biological properties such as antimicrobial, antifungal and acaricide and can be used to control pests in crops. One of the most targeted pests, as it ravages several crops, is Tetranychus urticae (Koch, 1836), popularly known as the two-spotted mite, which can multiply quickly, causing damage to plants and subsequently to fruits. Thus, the objective of this work was to use essential oils from the Lameaceae family, these being: basil oils (Ocimum basilicum L.), mint (Mentha piperita L.), oregano (Origanum vulgare L.) and thyme (Thymus vulgaris L.) as a method of managing T. urticae. In addition to evaluating the acaricidal potential of each of these essential oils, blends and major compounds of these essential oils were tested. Two-spotted mites were bred on jack bean plants under laboratory conditions. The essential oils were purchased commercially and the identification of the compounds was carried out by gas chromatography with a flame ionization detector (GC/DIC) and by gas chromatography coupled to mass spectrometry (GC/MS). The main constituents of the essential oils identified in the GC/MS were, estragole (91.8%) in basil oil, menthol (39.11%) in mint oil, carvacrol (76.80%) in oregano oil and thymol (45.76%) in thyme oil. The tests were carried out with essential oils, blends and their major compounds using the fumigation method, with basil oil (LC50= 8.02 μL.L-1 and CL90=27.30 μL.L-1), blend 8 (basilicon+oregano) (LC50= 7.21 μL.L-1 and LC90=15.66 μL.L-1) and ursol (LC50= 6.38 μL.L-1 and LC90=41.78 μL.L -1) showed greater toxicity to the two-spotted mite. Another method used was contact presenting oregano (LC50= 5.79 μL.mL-1 and CL90=11.25 μL.mL-1), blend 6 (thyme+basil) (LC50= 20.13 μL.mL -1 and LC90=46.42 μL.mL-1) and carvacrol (LC50= 19.46 μL.mL-1 and LC90= 33.82 μL.mL-1) with greater lethality against the two-spotted mite. After the end of the evaluations, the study showed that essential oils, blends and major compounds presented acaricidal potential for controlling the two-spotted mite, thus being an alternative for organic cultivation. However, studies are needed on contact action and repellency as well as its phytotoxicity to plants, studies that are currently underway.